Preparation method of iron-cobalt nano-alloy electrocatalyst
Cobalt-doped iron oxides were prepared by solvent-thermal method and low temperature thermal reduction method, which solved the problems of high reaction conditions and low electrocatalytic performance in the preparation of iron-cobalt alloys, and achieved high-efficiency electrocatalytic nitrate reduction in a wide range of environments. Highly active and efficient iron-cobalt nano alloy electrocatalyst.
Patent Information
- Application Number
- CN202411203009.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The existing iron-cobalt alloy preparation methods have high requirements for reaction conditions, and cannot synthesize uniform small particle size and low electrocatalytic performance, which cannot meet the requirements of electrocatalytic nitrate reduction of neutral electrolytes.
By using solvent-thermal method and low-temperature thermal reduction method, the iron salt and cobalt salt precursor are dispersed in the water-base-alcohol-organic acid system, the cobalt-doped iron oxide is formed and heat treatment is obtained in a reducing atmosphere, so that the size is uniform and Iron-cobalt nanoalloy electrocatalyst with adjustable proportion of metal elements.
It realizes high-efficiency electrocatalytic reduction of nitrate in a wide potential range, wide electrolyte concentration and wide nitrate concentration environment, with the performance advantages of high activity, high selectivity and high Faraday efficiency, and simplifies the process flow, reduces energy consumption and cost.
Smart Images

Figure CN119237722A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal nanomaterial preparation, in particular to a method for preparing an iron-cobalt nano alloy electrocatalyst. Background Art
[0002] Nitrate (NO3 - ) pollutants are common byproducts of industrial and agricultural activities and have become one of the most important environmental pollution and disease risk factors in the world. Ammonia (NH3) is a key raw material in the agricultural and chemical industries, and is also one of the ideal "zero-carbon" energy carriers in future sustainable energy. It is one of the most important chemicals in the world and has extremely high economic added value. Therefore, how to electrochemically reduce nitrate pollutants in water bodies to value-added ammonia is crucial to the sustainable development of modern agriculture and industry. Nitrate reduction to ammonia is a multi-electron process that requires a very high overpotential. Designing new, efficient and inexpensive non-precious metal catalysts is the key to achieving an efficient nitrate reduction to ammonia process.
[0003] In recent years, iron-based and cobalt-based inorganic metal nanomaterials have been widely used in the electrocatalytic nitrate reduction reaction to produce ammonia (NO3 - RR) showed excellent electrochemical catalytic activity, however, the Fe-Co alloy was used for electrocatalytic NO3 - However, there are few reports on RR research. Due to the similar atomic sizes of iron and cobalt, iron-cobalt alloys can form infinite solid solutions, thus showing a variety of existence forms, such as: Co3Fe7, CoFe, Co7Fe3, Co 0.72 Fe 0.28 Etc. If the type of iron-cobalt precursor and the preparation conditions are not effectively regulated, it is usually difficult to obtain an iron-cobalt alloy with uniform size distribution, which is not conducive to the study of the physical and chemical properties and catalytic mechanism of the iron-cobalt alloy. In addition, after the two different materials are coupled to form a heterojunction, they can give full play to their respective strengths and produce excellent synergistic effects, especially the atomic-level heterojunction interface is a concentrated distribution area of high reactivity. While forming an infinite solid solution, the iron-cobalt alloy will form a large number of defects, resulting in strong grain boundary and interface effects. However, the large size of the iron-cobalt alloy leads to a low specific surface area of the material, and also greatly reduces the number of exposed atomic-level interface active sites. In summary, the construction of an iron-cobalt alloy with uniform, small size and adjustable composition is very important for obtaining efficient NO3 - RR catalysts have important research and application value.
[0004] For the existing Co3Fe7 nanoalloy preparation method: the method described in the Chinese patent with publication number CN109215921A requires electrospinning / high temperature reduction method (500°C), which has high equipment requirements and is time-consuming, and the prepared Co3Fe7 particles have a larger particle size (50-100nm). The hydrothermal / high temperature pyrolysis method (800°C) described in the Chinese patent with publication number CN116815235A can only obtain Co3Fe7 particles with larger particles and uneven size distribution (1-10μm). Similarly, document 1 [Chemical Engineering Journal, 2022, 429, 132174] uses a sol-gel / high temperature reduction method (850°C) to prepare Co3Fe7 particles with larger particle size (20-100nm) and uneven size. Reference 2 [Advanced Science, 2020, 7, 2000747] uses a foam adsorption / high temperature reduction method (900°C) to obtain Co3Fe7 particles with an average size of about 100 nm. Reference 3 [NanoEnergy, 2021, 86, 106111] describes a dopamine polymerization coating / high temperature reduction method (800°C), which can obtain smaller Co3Fe7 particles (10-20 nm), but the preparation process is cumbersome, energy consumption is high, and the yield is low.
[0005] Preparation methods of iron-cobalt nano alloys with different element ratios:
[0006] 1. CoFe alloy: The method described in the Chinese patent with publication number CN116885218A uses a polymerization reaction to load Co and Fe metal precursor salts onto g-C3N4 and then calcines at high temperature (900°C). The prepared CoFe alloy particles are large in size and unevenly distributed (20-200nm). Document 4 [Chemical Engineering Journal, 2021, 420, 130516] obtains CoFe nanoalloys loaded on a carbon matrix by high-temperature pyrolysis (1000°C) of CoFe-MOFs (metal organic framework) precursors, and the particle size is large (100-300nm).
[0007] 2. Co7Fe3 alloy: The method described in the Chinese patent with publication number CN109926083A uses sodium borohydride to reduce soluble Fe salts and Co salts at room temperature under inert gas to prepare Co7Fe3 alloy particles with a particle size of 50 to 200 nm. Document 5 [Nano Research, 2023, 16, 2519-2527] obtains nitrogen-doped carbon-coated Co7Fe3 nano alloys by high-temperature pyrolysis (900°C) of ZnCoFe-ZIF (zeolite imidazolate framework) precursors, with a particle size of 5 to 50 nm, a large size distribution difference and a low yield. The above methods are complex in process, have high energy consumption requirements for equipment, are not conducive to large-scale production, and cannot prepare uniform, small-sized (<10 nm) iron-cobalt nano alloy particles with adjustable metal element ratios.
[0008] Up to now, there is no literature or published patent on the preparation method of synthesizing iron-cobalt nanoalloys with uniform size, small particle size and adjustable metal element ratio for electrocatalytic nitrate reduction in neutral electrolyte. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing an iron-cobalt nano alloy electrocatalyst, so as to solve the problems that the existing iron-cobalt alloy preparation method has high requirements on reaction conditions, cannot synthesize uniform small particle size and has low electrocatalytic performance.
[0010] The technical solution of the present invention is:
[0011] A method for preparing an iron-cobalt nano alloy electrocatalyst, the specific steps are as follows:
[0012] (1) dispersing different proportions of iron salt and cobalt salt precursors in water to form a suspension A, dispersing a base in a mixed solution of alcohol and an organic acid and stirring to form a soap B, pouring the suspension A into the soap B and stirring and mixing until the soap B is fully dissolved to form a suspension C;
[0013] The iron salt used is one or more of ferric acetylacetonate, ferric chloride, ferric nitrate and ferric sulfate containing trivalent iron ions, and the required molar concentration range of the iron salt is 0.01-0.50 mol / L; the cobalt salt used is one or more of cobalt acetylacetonate, cobalt chloride, cobalt nitrate and cobalt sulfate containing trivalent cobalt ions, and the required molar concentration range of the cobalt salt is 0.01-0.50 mol / L;
[0014] (2) pouring the suspension C into the inner tank of a solvent thermal reactor and sealing it, then maintaining it at a set temperature for a certain period of time to form iron-cobalt oxide, and obtaining cobalt-doped iron oxide precursor nanoparticles after cooling, washing and drying;
[0015] (3) Placing the cobalt-doped iron oxide precursor nanoparticles in a tubular furnace in a reducing atmosphere and maintaining them at a set temperature for a certain period of time, and obtaining the target iron-cobalt nanoalloy electrocatalyst after cooling, wherein the particle size ranges from 5 to 500 nm; the iron-cobalt nanoalloy electrocatalyst comprises the following components in atomic percentages, wherein cobalt is 0.01% to 99.99% and the remainder is iron.
[0016] In the method for preparing the iron-cobalt nano alloy electrocatalyst, in step (1), the iron salt is preferably iron acetylacetonate, and its molar concentration is preferably 0.06 mol / L; the cobalt salt is preferably cobalt acetylacetonate, and its molar concentration is preferably 0.04 mol / L.
[0017] The method for preparing the iron-cobalt nano alloy electrocatalyst comprises the following steps: in step (1), in order to obtain an electrocatalyst with uniform size and controllable morphology, the volume range of water in the raw material is 20 to 80 mL, the mass range of alkali in the raw material is 0.5 to 4.0 g, the volume range of the mixed solution of alcohol and organic acid in the raw material is 20 to 80 mL, and the mixed volume ratio range of alcohol and organic acid is 0.2 to 5.0.
[0018] In the method for preparing the iron-cobalt nano alloy electrocatalyst, in step (1), the volume of water in the raw material is preferably 40 mL, the mass of the alkali in the raw material is preferably 2.0 g, the volume of the mixed solution of alcohol and organic acid in the raw material is preferably 40 mL, and the mixed volume ratio of alcohol to organic acid is preferably 1.0.
[0019] The preparation method of the iron-cobalt nano alloy electrocatalyst, in step (1), the alkali used is one or more of sodium hydroxide, potassium hydroxide, and ammonia water, the alcohol used is one or more of methanol, ethanol, and ethylene glycol, and the organic acid used is one or more of oleic acid, linoleic acid, and stearic acid.
[0020] In the method for preparing the iron-cobalt nano alloy electrocatalyst, in step (1), the base used is preferably sodium hydroxide, the alcohol used is preferably ethanol, and the organic acid used is preferably oleic acid.
[0021] The method for preparing the iron-cobalt nano alloy electrocatalyst comprises the following steps: in step (2), a solvothermal method is used to prepare an iron-cobalt oxide precursor; the material of the reaction kettle used for the solvothermal reaction is one of stainless steel, aluminum alloy, copper and tantalum; the inner liner of the reaction kettle is one of polytetrafluoroethylene (PTFE) and high-density polyethylene (HDPE); the capacity of the inner liner ranges from 50 mL to 200 mL; the temperature range of the solvothermal reaction is from 140 to 220° C.; and the reaction time ranges from 2 to 24 hours.
[0022] In the method for preparing the iron-cobalt nano alloy electrocatalyst, in step (2), the temperature of the solvothermal reaction is preferably 180° C., and the reaction time is preferably 10 h.
[0023] The method for preparing the iron-cobalt nano alloy electrocatalyst comprises the following steps: in step (3), a low-temperature thermal reduction method is used to prepare the target iron-cobalt nano alloy electrocatalyst, wherein: the heating rate of the tubular furnace is in the range of 0.5 to 10° C. / min, the insulation temperature is in the range of 50 to 1100° C., and the insulation time is in the range of 0.5 to 24 h; the reducing atmosphere of the tubular furnace is one of the following: an ammonia / argon mixed gas, wherein the ammonia volume accounts for 5% to 100%; an ammonia / nitrogen mixed gas, wherein the ammonia volume accounts for 5% to 100%; a hydrogen / argon mixed gas, wherein the hydrogen volume accounts for 5% to 100%; a hydrogen / nitrogen mixed gas, wherein the hydrogen volume accounts for 5% to 100%.
[0024] In the method for preparing the iron-cobalt nano alloy electrocatalyst, in step (3), the heating rate of the tubular furnace is preferably 5° C. / min, the insulation temperature is preferably 350° C., and the insulation time is preferably 2 h.
[0025] The design ideas of the present invention are as follows:
[0026] Based on the special requirements of electrocatalytic reactions for catalyst active sites, charge and material transfer, combined with the process and cost optimization goals for large-scale applications, iron-cobalt nanoalloy electrocatalysts are obtained through a simple synthetic operation method using abundant, cheap and readily available non-precious metal raw materials.
[0027] The preparation process and characteristics of the material in the present invention are as follows: (1) using different proportions of iron source and cobalt source as reaction raw materials, dispersing them uniformly in a water-alkali-alcohol-organic acid system, pouring them into a hydrothermal reactor, heating them to a set temperature and reacting for a period of time, and then cooling, washing and drying to obtain a cobalt-doped iron oxide precursor; (2) heat-treating the oxide precursor in a tubular furnace in a reducing atmosphere, and obtaining an iron-cobalt nano alloy electrocatalyst (particle size 10 to 20 nm) after cooling.
[0028] Compared with the prior art, the present invention adopts a general solvothermal method and a low-temperature thermal reduction method, and synthesizes an iron-cobalt nano-alloy electrocatalyst with uniform size and adjustable metal element ratio by regulating the morphology of the cobalt-doped iron oxide precursor and the solvothermal and thermal reduction temperatures, etc. The iron-cobalt nano-alloy electrocatalyst synthesized by this method not only realizes efficient electrocatalytic reduction of nitrate to produce ammonia in a wide potential range, wide electrolyte concentration, and wide nitrate concentration water environment, but also has the performance advantages of high activity, high selectivity, and high Faraday efficiency for electrocatalytic reduction of nitrate to produce ammonia.
[0029] The advantages and beneficial effects of the present invention are:
[0030] 1. The iron-cobalt nano alloy electrocatalyst synthesized by the method of the present invention has excellent electrocatalytic nitrate reduction activity in a neutral electrolyte environment, and can achieve a high nitrate removal rate, synthetic ammonia selectivity and Faraday efficiency at a low overpotential.
[0031] 2. The iron-cobalt nano alloy electrocatalyst synthesized by the method of the present invention has a wide range of applicability and can be used in a wide range of potentials and NO3 - Effective catalysis can be achieved in electrolytes with a wide range of electrolyte concentrations.
[0032] 3. The present invention uses a solvent thermal method in a water-alkali-alcohol-organic acid system to synthesize a cobalt-doped iron oxide precursor, and then obtains an iron-cobalt nano alloy electrocatalyst by low-temperature thermal reduction treatment. This method can be carried out under general hydrothermal conditions and low-temperature thermal reduction conditions, and also has the production advantages of simple operation, simple process, short preparation cycle, low cost, and low energy consumption, and has the potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 :Iron-based nanometal particles (Fe), iron-cobalt nanoalloy particles doped with different proportions of cobalt (Co x Fe 1-x , x represents the addition of cobalt raw materials in different molar ratios, wherein the total molar amount of the metal raw materials is 4.0 mmol), XRD spectrum of cobalt-based nanometal particles (Co). In the figure, the horizontal axis 2θ represents the diffraction angle (°), and the vertical axis Intensity represents the intensity (au).
[0034] Figure 2 :(a) Iron-based nanometal particles (Fe), (b) to (j) iron-cobalt nanoalloy particles with different cobalt doping ratios (Co x Fe 1-x ), (k) Comparison of morphology of cobalt-based nanometal particles (Co) under scanning electron microscope.
[0035] Figure 3 :The structure of the optimal iron-cobalt nanoalloy particles (Co3Fe7) under atomic resolution spherical aberration electron microscopy (a), (b) and energy spectrum analysis (c).
[0036] Figure 4 :Comparison of polarization curves (a) and Tafel slopes (b) of electrocatalytic nitrate reduction to ammonia by iron-based nanometal particles (Fe), optimal iron-cobalt nanoalloy particles (Co3Fe7), and cobalt-based nanometal particles (Co). (a) In the figure, the horizontal axis Potential vs. RHE represents the potential (V), and the vertical axis current density represents the current density (mA / cm 2 ); (b) In the figure, the horizontal axis Log j represents the current density (mAcm-2 ), and the ordinate Potential vs. RHE represents the potential (V).
[0037] Figure 5 :Cobalt doped iron-cobalt nano alloy particles with different proportions x Fe 1-x At 500ppm NO3 - -N+0.1M Na2SO4 electrolyte at -0.69V (vs.RHE) electrolysis-time (it) test 9h NO3 - Removal rate and synthetic ammonia selectivity comparison. In the figure, the horizontal axis Doping amount of Co represents the Co doping amount (%), and the left vertical axis NO3 - removalefficiency represents NO3 - Removal rate (%) corresponds to the value on the left side of each group, and the vertical coordinate Selectivity for NH3 on the right side represents the selectivity of synthetic ammonia (%), corresponding to the value on the right side of each group.
[0038] Figure 6 : Optimal Co3Fe7 alloy in 500ppm NO3 over a wide range of reduction potentials - -N+0.1M Na2SO4 electrolyte for NO3 - Removal rate, Faraday efficiency and synthetic ammonia selectivity. In the figure, the horizontal axis Potential vs. RHE represents the potential (V), and the vertical axis NH3 yield rate on the left represents the ammonia yield (μg h -1 cm -2 ), the right vertical axis Percentage represents the Faradaic efficiency or synthetic ammonia selectivity (%); each group from left to right is: yield rate represents ammonia yield, Faradaic efficiency represents Faradaic efficiency (FE), Selectivity represents synthetic ammonia selectivity.
[0039] Figure 7 : Optimal Co3Fe7 alloy in 500ppm NO3 over a wide electrolyte concentration range - -0.69V (vs.RHE)it test 9h NO3 - Removal rate and synthetic ammonia selectivity. In the figure, the horizontal axis Concentration of Na2SO4 represents the molar concentration of sodium sulfate (M), and the left vertical axis NO3 - removal efficiency represents NO3 -Removal rate (%) corresponds to the value on the left side of each group, and the vertical coordinate Selectivity for NH3 on the right side represents the selectivity of synthetic ammonia (%), corresponding to the value on the right side of each group.
[0040] Figure 8 : Wide NO3 - The optimal Co3Fe7 alloy under the concentration range was tested in 0.1M Na2SO4 electrolyte at -0.69V (vs.RHE) for 3h in NO3 - Removal rate, Faraday efficiency and synthetic ammonia selectivity. In the figure, the horizontal axis is NO3 - -NConcentration represents the NO3 in the electrolyte - -N concentration (ppm), the left vertical axis NH3 yield rate represents the ammonia yield (μg h -1 cm -2 ), the right vertical axis Percentage represents the Faradaic efficiency or synthetic ammonia selectivity (%); each group from left to right is: yield rate represents ammonia yield, Faradaic efficiency represents Faradaic efficiency (FE), Selectivity represents synthetic ammonia selectivity. DETAILED DESCRIPTION
[0041] In the specific implementation process, iron-based nano-metal particles (referred to as Fe), iron-cobalt nano-alloy particles doped with different concentrations of cobalt (referred to as Co) x Fe 1-x ), cobalt-based nanometal particles (abbreviated as Co) were used as comparison objects. 0.4 Fe 0.6 (The crystal structure is Co3Fe7, the molar ratio of iron to cobalt is 0.6:0.4, x=0.4, and the total molar amount of the metal raw material is 4.0mmol): In a 100mL polytetrafluoroethylene reactor liner, add 20mL ethanol and 20mL oleic acid and stir, then add 2g NaOH, wait for it to react and solidify into a soap-like substance. Take 848mg (2.4mmol) of ferric acetylacetonate and 570mg (1.6mmol) of cobalt acetylacetonate and disperse them in 40mL of deionized water, and pour them into the above reactor liner. Use a glass rod to stir until the soap-like substance is initially dissolved, then stir continuously for 10min with a stirrer until it is fully dissolved, and remove the stirrer. The above polytetrafluoroethylene reactor liner is sealed and placed in a stainless steel shell, placed in an oven and heated to 180℃ for 10h. After cooling to room temperature, pour off the upper emulsion, collect the bottom precipitate in a centrifuge tube, and centrifuge at a speed of 12000r / min for 5min. The samples were washed with deionized water and ethanol respectively under the same centrifugal conditions for two times, and then dried under vacuum at 60 °C to obtain the precursor Cox Fe 3-x O4 nanoparticles. The precursor was ground into powder in an agate mortar, placed in a porcelain ark, and heated to 350°C at a rate of 5°C / min in a tubular furnace in a reducing atmosphere (hydrogen / argon mixed gas, with hydrogen accounting for 5% by volume), and kept warm for 2 hours. After cooling to room temperature, the sample was taken out and ground again with an agate mortar to obtain an iron-cobalt nanoalloy catalyst. For pure iron and pure cobalt metals, only acetylacetonate iron or acetylacetonate cobalt was used instead, and the other conditions remained unchanged. Other iron-cobalt alloys with different iron-cobalt metal element ratios were prepared using different molar ratios of acetylacetonate iron and cobalt acetylacetonate.
[0042] The present invention is further described in detail below through examples and drawings.
[0043] Example 1
[0044] The iron-based nanoparticles (Fe for short) and the iron-cobalt nanoparticles (Co for short) doped with different concentrations of cobalt were used to prepare the nanoparticles. x Fe 1-x ), cobalt-based nanometal particles (abbreviated as Co) were used as comparison objects, and the physical phases of the samples prepared by this method were studied.
[0045] X-ray test equipment and conditions: Rigaku D / max 2500 X-ray diffractometer, Cu Ka ray. Figure 1 As shown in the figure, Fe and Co 0.1 Fe 0.9 、Co 0.2 Fe 0.8 、Co 0.3 Fe 0.7 、Co 0.4 Fe 0.6 (Crystal structure is Co3Fe7), Co 0.5 Fe 0.5 、Co 0.6 Fe 0.4 、Co 0.7 Fe 0.3 、Co 0.8 Fe 0.2 、Co 0.9 Fe 0.1 Among them, in a series of reported X-ray diffraction PDF cards related to cobalt-iron alloys, the Co3Fe7 card not only has the same diffraction peak position as Co 04 Fe 06 The most matched, and the molar ratio in the chemical formula is also the most similar, so it is believed that Co 0.4 Fe 0.6The crystal structure is Co3Fe7. The spectrum shows that pure iron particles are obtained without cobalt addition, and a series of iron-cobalt nano-alloy particles with different concentrations of cobalt doped will be obtained according to the concentration of cobalt addition, and cobalt metal particles will be obtained if only cobalt is added.
[0046] Example 2
[0047] The iron-based nanoparticles (Fe for short) and the iron-cobalt nanoparticles (Co for short) doped with different concentrations of cobalt were used to prepare the nanoparticles. x Fe 1-x ) and cobalt-based nanometal particles (abbreviated as Co) were used as comparison objects, and the morphology of the samples prepared by this method was studied.
[0048] Morphology characterization equipment: FEI Nova620 scanning electron microscope. Figure 2 As shown in Figures (a), (b), (c), (d), (e), (f), (g), (h), (i), (j), and (k) are Fe, Co 0.1 Fe 0.9 、Co 0.2 Fe 0.8 、Co 0.3 Fe 0.7 、Co 0.4 Fe 0.6 (Crystal structure is Co3Fe7), Co 0.5 Fe 0.5 、Co 0.6 Fe 0.4 、Co 0.7 Fe 0.3 、Co 0.8 Fe 0.2 、Co 0.9 Fe 0.1 , Co micromorphology. As shown in Figure (a), the synthesized Fe is a homogeneous substance with a particle size of 20 to 40 nm. As shown in Figures (b) to (j), the size distribution of the synthesized iron-cobalt nanoalloy particles is uniform. Adding Co within an appropriate range (0% to 30at%) can significantly reduce the size of the catalyst particles (a to d, 10 to 40 nm), while adding excessive amounts (50at% to 90at%) can significantly increase the particle size (g to j, 20 to 100 nm). As shown in Figure (k), the particle size of the synthesized Co is about 20 nm.
[0049] Example 3
[0050] Cobalt-doped iron-cobalt nanoparticles with optimal electrocatalytic performance 0.4 Fe 0.6 (The crystal phase structure is Co3Fe7) was taken as the research object, and the crystal structure prepared by this method was studied.
[0051] Morphology characterization equipment: ARM200F spherical aberration corrected transmission electron microscope. Figure 3 As shown, Figures (a) and (b) are atomic-level resolution images of Co3Fe7, the upper left corner is the corresponding diffraction pattern, and the lower right corner is the corresponding crystal model. From Figures (a) to (b), it can be seen that the clear high-resolution pattern and the single diffraction spot type clearly prove that the particle is a single crystal and is completely consistent with the crystal model, confirming the effectiveness of the preparation method of the synthetic cobalt-doped iron-cobalt nanoalloy particles (Co3Fe7). Figure (c) is an energy spectrum image of Co3Fe7, which clearly shows the uniform distribution of Fe and Co elements and a portion of surface adsorbed oxygen.
[0052] Example 4
[0053] Iron-based nanometal particles (referred to as Fe), optimal cobalt-doped iron-cobalt nanoalloy particles Co 0.4 Fe 0.6 (Crystal structure is Co3Fe7) and cobalt-based nanometal particles (abbreviated as Co) are taken as research objects to study the effect of cobalt doping on the starting potential, current density and Tafel slope of electrocatalytic nitrate reduction in neutral electrolyte of iron-cobalt nanometal particles.
[0054] Neutral electrolyte electrocatalytic nitrate reduction test: (1) Preparation of catalyst ink: 10 mg sample and 2 mg conductive carbon black were dispersed in a mixed solution of 600 μL deionized water and 350 μL isopropanol, and 50 μL of Nafion solution with a mass concentration of 5% was dropped into it. Ultrasonication was performed for 30 min to form a uniform catalyst ink. (2) Preparation of working electrode: 200 μL of catalyst ink was dripped on 1.5 cm × 1.5 cm hydrophilic carbon paper (TORAY, TGP-H-060) twice and dried under an infrared lamp at 60 ° C. (3) Configuration of H-type electrolytic cell: A proton exchange membrane (DUPONT, N211) was clamped at the connection of an H-type electrolytic cell with a single cell volume of 70 mL, and 50 mL of a sodium sulfate solution with a molar concentration of 0.1 M and a solution containing 500 ppm NO3 were poured into each side. — N molar concentration of 0.1M sodium sulfate solution and insert a platinum electrode as the counter electrode and a silver-silver chloride electrode as the reference electrode. (4) LSV curve test: EC-Lab VSP 300 electrochemical workstation was used for testing, with a scan speed of 5mV / s and a scan range of 0V to -0.9V (vs. RHE). The test results are shown in Figure 4As shown in Figures (a) and (b), the electrochemical polarization curves and corresponding Tafel slope curves of Fe, Co3Fe7, and Co are shown respectively. As can be seen from Figure (a), the starting potential of Co3Fe7 is significantly improved compared with Fe, and the current density of Co3Fe7 is significantly improved compared with Co. As can be seen from Figure (b), the Tafel slope of Co3Fe7 is the lowest, indicating that it has a faster electrocatalytic kinetic process. Both figures confirm that Co3Fe7 has the best electrocatalytic nitrate reduction to ammonia performance.
[0055] Example 5
[0056] The nanostructured Fe-based metal particles (referred to as Fe) and cobalt-doped nanostructured cobalt-iron solid solution particles (referred to as Co) were used to prepare the nanostructured Fe-based metal particles. x Fe 1-x ) and cobalt-based nanometal particles (abbreviated as Co) were used as comparison objects to study the effect of cobalt doping on the removal rate and selectivity of neutral electrocatalytic nitrate reduction reaction of iron-based nanometal particles.
[0057] Neutral electrolyte electrocatalytic nitrate reduction test: (1) Test preparatory work see Example 4. (2) It curve test: Time-current curve test was performed at a constant potential of -0.69 V (vs. RHE), stopping every 3 hours and taking a small amount of electrolyte for dilution, and continuing until the 9th hour. (3) Spectroscopic specific detection of NO3 - 、NO2 - NH4 + :1. Configure a series of NO3 concentration gradients - 、NO2 - NH4 + 2. By measuring the absorption spectrum of the electrolytes that react for different time periods, the results are brought into the absorbance-concentration standard baseline to calculate the NO3 in the electrolytes with different reaction times. - 、NO2 - NH4 + The concentration of Figure 5 As shown. Figure 5 It can be seen that NO3 - The removal rate and the selectivity of synthetic ammonia are distributed in a volcanic shape with the doping ratio, indicating that the electrocatalytic nitrate reduction to ammonia production performance is the best when Co raw material (i.e. Co3Fe7) is added, and 97.8% of NO3 - Removal efficiency and 99.8% ammonia selectivity.
[0058] Embodiment 6-8
[0059] Co with the best electrocatalytic performance 0.4 Fe 0.6As a research object, the NO3 - Removal rate, Faradaic efficiency and selectivity of synthetic ammonia.
[0060] Neutral electrolyte electrocatalytic nitrate reduction test: (1) Test preparatory work see Example 4. (2) IT curve test and spectroscopic specific detection conditions: see Example 5. Test results are as follows Figure 6-Figure 8 As shown, Figure 6 , Figure 7 , Figure 8 Respectively represent Co 04 Fe 06 In the wide range of reduction potential (-0.49 to -0.89 V), wide range of electrolyte (sodium sulfate molar concentration 0.02 to 0.2 M), wide range of nitrate concentration (NO3 — N concentration of 50 to 1000 ppm) has excellent nitrate reduction performance.
[0061] The results of the examples show that the method for preparing the iron-cobalt alloy nanoparticles provided by the present invention can effectively improve the neutral nitrate reduction performance of the iron-based nanometal particles by doping with cobalt. 0.4 Fe 0.6 The catalyst can achieve excellent NO3 - Removal rate, Faraday efficiency and synthetic ammonia selectivity. Compared with the reported iron- and cobalt-based neutral nitrate reduction electrocatalysts, it has the advantages of better performance, more efficient reaction, more energy-saving process and simpler synthesis method, and has potential value for large-scale promotion. In addition, this method also has an important reference role in the preparation of more types of transition metal-based nanoalloys with certain morphologies in the future.
Claims
1. A method for preparing an iron-cobalt nano alloy electrocatalyst, characterized in that: The specific steps are as follows: (1) dispersing different proportions of iron salt and cobalt salt precursors in water to form a suspension A, dispersing a base in a mixed solution of alcohol and an organic acid and stirring to form a soap B, pouring the suspension A into the soap B and stirring and mixing until the soap B is fully dissolved to form a suspension C; The iron salt used is one or more of ferric acetylacetonate, ferric chloride, ferric nitrate and ferric sulfate containing trivalent iron ions, and the required molar concentration range of the iron salt is 0.01-0.50 mol / L; the cobalt salt used is one or more of cobalt acetylacetonate, cobalt chloride, cobalt nitrate and cobalt sulfate containing trivalent cobalt ions, and the required molar concentration range of the cobalt salt is 0.01-0.50 mol / L; (2) pouring the suspension C into the inner tank of a solvent thermal reactor and sealing it, then maintaining it at a set temperature for a certain period of time to form iron-cobalt oxide, and obtaining cobalt-doped iron oxide precursor nanoparticles after cooling, washing and drying; (3) Placing the cobalt-doped iron oxide precursor nanoparticles in a tubular furnace in a reducing atmosphere and maintaining them at a set temperature for a certain period of time, and obtaining the target iron-cobalt nanoalloy electrocatalyst after cooling, wherein the particle size ranges from 5 to 500 nm; the iron-cobalt nanoalloy electrocatalyst comprises the following components in atomic percentages, wherein cobalt is 0.01% to 99.99% and the remainder is iron.
2. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 1, characterized in that: In step (1), the iron salt is preferably iron acetylacetonate, and its molar concentration is preferably 0.06 mol / L; the cobalt salt is preferably cobalt acetylacetonate, and its molar concentration is preferably 0.04 mol / L.
3. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 1, characterized in that: In step (1), in order to obtain an electrocatalyst with uniform size and controllable morphology, the volume range of water in the raw material is 20 to 80 mL, the mass range of alkali in the raw material is 0.5 to 4.0 g, the volume range of the mixed solution of alcohol and organic acid in the raw material is 20 to 80 mL, and the mixed volume ratio range of alcohol and organic acid is 0.2 to 5.
0.
4. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 3, characterized in that: In step (1), the volume of water in the raw material is preferably 40 mL, the mass of the alkali in the raw material is preferably 2.0 g, the volume of the mixed solution of alcohol and organic acid in the raw material is preferably 40 mL, and the mixed volume ratio of alcohol to organic acid is preferably 1.
0.
5. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 1 or 3, characterized in that: In step (1), the alkali used is one or more of sodium hydroxide, potassium hydroxide, and ammonia water, the alcohol used is one or more of methanol, ethanol, and ethylene glycol, and the organic acid used is one or more of oleic acid, linoleic acid, and stearic acid.
6. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 5, characterized in that: In step (1), the base used is preferably sodium hydroxide, the alcohol used is preferably ethanol, and the organic acid used is preferably oleic acid.
7. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 1, characterized in that: In step (2), a solvothermal method is used to prepare an iron-cobalt oxide precursor. The material of the reaction kettle used for the solvothermal reaction is one of stainless steel, aluminum alloy, copper and tantalum. The inner liner of the reaction kettle is one of polytetrafluoroethylene (PTFE) and high-density polyethylene (HDPE); the capacity of the inner liner ranges from 50 mL to 200 mL, the temperature range of the solvothermal reaction is 140 to 220° C., and the reaction time range is 2 to 24 h.
8. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 7, characterized in that: In step (2), the temperature of the solvothermal reaction is preferably 180° C., and the reaction time is preferably 10 h.
9. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 1, characterized in that: In step (3), a low-temperature thermal reduction method is used to prepare the target iron-cobalt nano-alloy electrocatalyst, wherein: the heating rate of the tubular furnace is in the range of 0.5 to 10°C / min, the insulation temperature is in the range of 50 to 1100°C, and the insulation time is in the range of 0.5 to 24h; the reducing atmosphere of the tubular furnace is one of the following: an ammonia / argon mixed gas, wherein the volume proportion of ammonia is 5% to 100%; an ammonia / nitrogen mixed gas, wherein the volume proportion of ammonia is 5% to 100%; a hydrogen / argon mixed gas, wherein the volume proportion of hydrogen is 5% to 100%; a hydrogen / nitrogen mixed gas, wherein the volume proportion of hydrogen is 5% to 100%.
10. The method for preparing the iron-cobalt nano alloy electrocatalyst according to claim 9, characterized in that: In step (3), the heating rate of the tubular furnace is preferably 5°C / min, the insulation temperature is preferably 350°C, and the insulation time is preferably 2h.
Citation Information
Patent Citations
Preparation method and application of composite cathode integrating efficient in-situ electrosynthesis of hydrogen peroxide and catalytic performance
CN112479317A
Preparation method and application of ferrocobalt / carbon paper self-supporting electrode material
CN114702107A
Preparation method of iron-cobalt bimetal derived carbon film electrode for electrocatalytic reduction of nitrate
CN115818794A
Composite slow-release material for repairing underground water polluted by organic matters as well as preparation method and application of composite slow-release material
CN117843117A
Nickel-iron-cobalt trimetal nano array electrocatalyst, method and application of nickel-iron-cobalt trimetal nano array electrocatalyst in electrocatalytic oxidation of 5-hydroxymethylfurfural
CN118385603A
Cited By
Nanometer zero-valent iron for synthesizing ammonia through electroreduction of nitrate radicals and preparation method and application of nanometer zero-valent iron
CN121087528A
